It seems likely you are asking about how to simplify this. (Please note the parentheses are necessary to make this mean what you want it to mean.)

(x

Both the numerator and the denominator can be factored.

(x

The terms (x+10)/(x+10) have a value of 1, so this expression is equivalent to

= ((x+4)/(x-10))*((x+10)/(x+10)) = ((x+4)/(x-10))*1

= (x+4)/(x-10)

(x

^{2}-14x +40)/(x^{2}-100)Both the numerator and the denominator can be factored.

(x

^{2}-14x +40)/(x^{2}-100) = ((x+4)(x+10))/((x-10)(x+10))The terms (x+10)/(x+10) have a value of 1, so this expression is equivalent to

= ((x+4)/(x-10))*((x+10)/(x+10)) = ((x+4)/(x-10))*1

= (x+4)/(x-10)